Croatian Ethnogenesis and the Nomadic Element - Heršak, Emil (Array, 2008)
In the paper, the authors present certain parameters dealing with the nomadic ele¬ment, or pos-sible indications of it, in Croatian ethnogenesis. First, a comment is given on the ethno¬genetic concept itself, and a working definition of ethnogenesis is suggested. Second, the major com¬ponents that are considered to have had a role in Croatian ethnogenesis are listed. This discussion is followed by an identification of those elements that could somehow be considered nomadic, or else representative of influences from the Eurasian steppe region. Mention is made of historical sources that confirm or im¬ply the presence of Eurasian nomad groups in the Croatian area, and the relative fre¬quency of archaeo¬logical material is noted. The authors analise views of previous and present Croatian and foreign au¬thors on Croatian ethnogenesis, especially in regard to the “Eurasian connection”. In this part of the dis¬cussion, the Iranian theory of Croat origins is presented in more detail. Finally, the authors briefly address recent genetic (DNA) analyses of the contemporary Croatian population.